Мethodical Recommendations for sampling and Preserving of gastrointestinal Nematodes of Ruminants - D. N. Kuznetsov (Российский паразитологический журнал, 2020)
The purpose of the research is improving the accuracy of studies of nematodes parasitizing in the digestive tract of ruminants. Materials and methods. The literature data and own research results concerning sampling and preserving of nematodes parasitizing various parts of gastrointestinal tract of domestic and wild ruminants have been analyzed. The possibility of using the samples of nematodes, both in morphological and molecular studies, has been taken into account. Results and discussion. The methods for sampling and preserving of gastrointestinal nematodes of ruminants are described in detail. The features of sampling nematodes parasitizing in various parts of the digestive tract are considered. The ways for minimizing of losses of nematode samples during helminthological necropsy are proposed. Using of 96% ethanol as a preserving liquid is recommended and allows the DNA study of samples.